PENGENDALIAN MOTOR DC BRUSHLESS DENGAN PID PADA ROBOT PENGHINDAR HALANGAN (OBSTACLE AVOIDANCE ROBOT) - Pribadi, Bayu Dadang; Widyantara, Helmy; Harianto, Harianto (Journal of Control and Network Systems, 2014)
Detection system using a robot to walk lot as a reference sensor to avoid obstacles in the application of obstacle avoidance robot get input from sensors Ultrasonic Distance to generate movement toward desired goals. Input can use camera as a sensor on the robot obstacle avoidance. Functions expected in a robot that has the ability to avoid an obstacle (obstacle avoidance) in order to achieve a mission of the robot, so the robot can walk with subtle needed a controller , which is used for system control is PID control with input parameters use the ping sensor Ultrasonic Distance. Ultrasonic Distance Sensor is a type of sensor that has output far distance range 3cm - 3 meters . The characteristics of this sensor can only be on a plane at an angle of 90 ° . In this research, the data output from the sensor will be processed on the Microcontroller to respond to the motor and control system are used as a rudder servo motor . In order to obstacle avoidance in front, left side, and, right then it needs to be added to the sensor on the front , right and left the base of the robot . Process the input from the sensors will provide information on where obstructions are . Ackreman steering system steering the robot as a solution to be able to avoid the obstacle . Setting speed on PID control can fix the sensor response to the hitch . In the calculation of this final plant PID worth Kp = 1 , Ki = 0 , Kd = 0.